2014
DOI: 10.7314/apjcp.2014.15.18.7817
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Childhood Cancers at a Regional Cancer Centre in North-East India

Abstract: Childhood cancers are relatively uncommon in comparison to adult cancers. There is no literature available to shed light on clinic-pathological types and patterns of care for childhood cancers in our population in North-East India. In this analysis we therefore tried to determine the common childhood cancers diagnosed in our institute, clinical profile of the patients, types of treatment and compliance, and median survival estimates. Leukemia was most common, followed by retinoblastoma, central nervous system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…In this study most of cases were in age group of 10-14 years (35%), Similar finding was seen in a study by Rajpal et al showed similar results in the age group of 10-14 years (58.18%) [14] .This result is contrary to study done by others in which most cases were between to 5-9 years age group [7,11,15]. Some Studies found most common age is 0-4 years [13,16].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study most of cases were in age group of 10-14 years (35%), Similar finding was seen in a study by Rajpal et al showed similar results in the age group of 10-14 years (58.18%) [14] .This result is contrary to study done by others in which most cases were between to 5-9 years age group [7,11,15]. Some Studies found most common age is 0-4 years [13,16].…”
Section: Discussionsupporting
confidence: 82%
“…This result is contrary to study done by Jabeen et al showed that Lymphoma (24.2%) followed by Retinoblastoma (17.4%), leukemia (14.3%) [10]. Study by Munlima et al showed that most common cancer group was leukemia (26.9%) followed by Retinoblastoma (15.9%), CNS tumour (14.5%), Lymphoma (13.1%) [11].…”
Section: Discussionmentioning
confidence: 68%
“…Globally, the incidence of cancer in children differs from 48 to 70 per million children less than 15 years of age [3]. The incidence of childhood cancer in some developed countries, such as in United State, Ireland, Switzerland, and in Australia has reported with rates of 15.3, 13, 13.5, and 16 per 100,000 children, respectively, however in Asia the data are generally lower [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The methodology in the remaining eight was not reported . Eight studies defined abandonment, ranging from missing two appointments to missing four weeks of therapy . Only 13 studies actively followed up cases of abandonment to minimize misclassification …”
Section: Overall Resultsmentioning
confidence: 99%
“…One hundred thirteen studies did not have a primary objective of investigating genetic/biochemical prognosticators; ARs were available for 38 (33.6%) of these studies (Supporting Information missing two appointments to missing four weeks of therapy. 5,6,[15][16][17][18][19][20] Only 13 studies actively followed up cases of abandonment to minimize misclassification. 5,6,11,15,16,18,[20][21][22][23][24][25][26]…”
Section: Overall Resultsmentioning
confidence: 99%